(untitled) (Communications in Computational Physics, 2020)
In this paper, a numerical investigation on heterogeneous catalysis is performed by means of a Regularized Lattice BGK approach. The effects of different values of the reactant flow Knudsen numbers are evaluated, in terms of conversion efficiency and penetration inside the structure of a nano-porous gold ingot. The results are in line with experimental evidence in the literature and open interesting perspectives for the optimal design of future nano-catalytic devices.